PERANCANGAN WEBSITE RESEP MAKANAN TRADISIONAL KHAS MINANGKABAU - LARAS ROBERT PANGESTU, Dr. Budiwiran, M.Pd., Hendra Afriwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Website is one of nowadays information media that provide any kinds of spoken, written, and verbal informations. People really like Minangkabau traditional food recipes Websites. But, these websites are not optimal yet.Minangkabau traditional food recipes Website contain some Minangkabau traditional food recipes that is not popular anymore. This website was designed informatively, comunicatively, and inovatively using visual communication design elements and principles. Design aims to help people who wants to learn Minangkabau traditional cook easier.The design method is black box method. The analysis approach is 5W+1H analysis (what, who, where, when, why, and how) to find the solution for the problems. The process starts by data collection and observation over the existing traditional food websites and interview some restaurant chef. The support media that is used to support the main media are poster, web banner, x-banner, recipe book, sticker, brochure, and banner.Keywords: Web design, Recipe, Traditional, Minangkabau